PENERAPAN JIGSAW COOPERATIVE LEARNING PADA MATERI ANALISIS KOMPONEN EKOSISTEM DAN INTERAKSINYA DI KELAS X - Wakhid, Heru Akbar Nur; Setyawan, Danang Budi (Prosiding Temu Ilmiah Nasional Guru, 2023)
This study aims to determine the application of the jigsaw cooperative learning model in the material of analyzing components and interactions between components in class X. The use of an inappropriate learning model affects the effectiveness and activeness of students during the learning process. An ecosystem is a complex interrelationship between living things and their environment. In this study using the jigsaw model, this model is based on the principle of collaboration and cooperation between students in groups to achieve learning goals together. The application of the Jigsaw learning model has several advantages, one of which is this model encourages collaboration and collaboration between students. They help each other, support, and are responsible for each other in achieving learning goals. The results showed that the application of the jigsaw cooperative learning model succeeded in increasing student activity during the learning process.